2015
DOI: 10.1103/physrevb.91.094512
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic and nematic phase transitions inBaFe2(As1xPx

Abstract: We study the antiferromagnetic (AFM) and structural phase transitions in single crystal BaFe 2 (As 1-x P x ) 2 ( 0, 0.3 x ) at temperatures T N and T S , respectively, by high resolution ac microcalorimetry and SQUID magnetometry. The specific heat measurements of both as grown and annealed BaFe 2 As 2 displays a sharp peak at the AFM/Structural transitions. A kink in the entropy of annealed BaFe 2 As 2 gives evidence for splitting of the two transitions by approximately 0.5K. No additional features could be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
5
7
0
Order By: Relevance
“…5(h)]. Since our neutron Larmor diffraction measurements showed no additional anomaly in lattice parameters and lattice distortion above T s , we conclude that there is no thermodynamic phase transition at T * and T * * in agreement with recent heat capacity measurements [21]. The resistivity anisotropy seen in the stress free detwinned samples below T * * on warming across T N is then due to local spin nematic correlations and associated lattice distortions arising from the magnetoelastic coupling through the collinear AF state below T N .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…5(h)]. Since our neutron Larmor diffraction measurements showed no additional anomaly in lattice parameters and lattice distortion above T s , we conclude that there is no thermodynamic phase transition at T * and T * * in agreement with recent heat capacity measurements [21]. The resistivity anisotropy seen in the stress free detwinned samples below T * * on warming across T N is then due to local spin nematic correlations and associated lattice distortions arising from the magnetoelastic coupling through the collinear AF state below T N .…”
Section: Resultssupporting
confidence: 78%
“…These results suggest that the resistivity anisotropy observed in the external uniaxial pressure free tetragonal state of BaFe 2−x Ni x As 2 arises from a strong magnetoelastic coupling induced by AF order, and such anisotropy would vanish in a strain free paramagnetic tetragonal phase. Furthermore, our data indicate no additional thermodynamic phase transitions above T s , consistent with earlier work [21,31]. Therefore, the Ising-nematic correlations, a state with no magnetic long-range order (stag-gered magnetization M = 0) but with local broken C 4 symmetry lattice distortion [32][33][34], is the driving force for the observed resistivity anisotropy (Fig.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…These observations are also consistent with finite orbital splitting persisting above the bulk transition found for unstressed Ba(Fe 1−x Co x ) 2 As 2 crystals by ARPES. 29 On the other hand, the recent high-resolution specific heat measurements 35 clearly excluded possibility of the bulk phase transition in this temperature range.…”
Section: 31mentioning
confidence: 98%
“…In contrast, Kasahara et al, reported that the magneto‐torque and X‐ray diffraction measurements on a micro‐sized single‐domain crystal of BaFe 2 (As,P) 2 show the nematic properties above the macroscopic crystallographic phase‐transition temperature T S even without any external pressure and suggested that a weak but static nematic phase transition should be detected in the specific heat measurement. However, no clear phase transition has been detected in the AC magneto‐calorimetry measurements on BaFe 2 (As,P) 2 above T S …”
mentioning
confidence: 98%